Effect of Guava Leaves Powder on the Oxidative and Microbial Stability of Chicken Meat Nuggets during Refrigerated (4±1°C) Storage - Kola, Manjula; Reddy G V, Bhaskar; Bandi, Kalyani; Donadi, Jhansi (Journal of Meat Science, 2026)
The present study was carried out to evaluate the efficacy of different levels (0.5 and 1 per cent) of guava leaf powder (GLP) (Psidium guajava L) with synthetic antioxidant ie) butylated hydroxy toluene (BHT) at 0.01 % was studied on physico-chemical, microbial and sensory quality characteristics of chicken meat nuggets under aerobic packaging conditions during refrigerated storage (4±1°C). The chicken nuggets added with 1 % GLP had significantly (P < 0.05) lower 2-thiobarbituric acid reactive substance (TBARS) values and free fatty acid (FFA) content compared to control nuggets and other samples during refrigerated storage (4±1°C). A significant (P<0.05) lower total plate count and total psychrophilic count were recorded in chicken nuggets added with GLP. Addition of 1 % GLP significantly (P<0.05) reduced the coliform count and yeast and mould counts than control and BHT added chicken nuggets. 1 per cent GLP added chicken meat nuggets rated significantly (P<0.05) superior scores of colour, flavor, tenderness, juiciness and overall acceptability than control, BHT and 0.5 % GLP added chicken meat nuggets. Based on the obtained results, it was concluded that 1 % GLP had excellent antioxidant and antimicrobial properties compared to control and BHT added chicken meat nuggets during refrigerated storage under aerobic conditions and application of GLP as natural antioxidant and anti microbial agent in chicken meat nuggets which extends shelf life up to 20 days in refrigerated storage without any quality deterioration.